Capital constraints, counterparty risk, and deviations from covered interest rate parity - Niall Coffey; Warren B. Hrung; Asani Sarkar (Federal Reserve Bank of New York, 2009)
We provide robust evidence of deviations from the covered interest rate parity (CIP) relation since the onset of the financial crisis in August 2007. The CIP deviations exist with respect to several different dollar-denominated interest rates and exchange rate pairings of the dollar vis-à-vis other currencies. The results show that our proxies for margin conditions and for the cost of capital are significant determinants of the CIP deviations. Following the bankruptcy of Lehman Brothers, uncertainty about counterparty risk became a significant determinant of CIP deviations. The supply of dollars by the Federal Reserve to foreign central banks via reciprocal currency arrangements (swap lines) reduced CIP deviations. In particular, the announcement on October 13, 2008, that the swap lines would become unlimited reduced CIP deviations substantially. These results indicate a breakdown of arbitrage transactions in the international capital markets during the crisis that stems partly from lack of funding and partly from heightened counterparty credit risk. Central bank interventions helped reduce the funding liquidity risk of global institutions.
Keywords: G10; G14; G15; G18; 330; Covered interest rate parity; funding constraints; counterparty credit risk; central bank currency swap lines; financial crisis; foreign exchange